Phasor Histone FLIM-FRET Microscopy Maps Nuclear-Wide Nanoscale Chromatin Architecture With Respect to Genetically Induced DNA Double-Strand Breaks - Lou, Jieqiong; Solano, Ashleigh; Liang, Zhen; Hinde, Elizabeth (Frontiers in Genetics, 2021)
A DNA double strand break (DSB) takes places in the context of chromatin and there is increasing evidence for chromatin structure to play a functional role in DSB signalling and repair. Thus there is an emerging need for quantitative microscopy methods that can directly measure chromatin network architecture and detect changes in this structural framework upon DSB induction within an intact nucleus. To address this demand, here we present the phasor approach to fluorescence lifetime imaging microscopy (FLIM) of Förster resonance energy transfer (FRET) bewteen fluorescently labelled histones in the DSB inducible via AsiSI cell system (DIvA), which has sufficient spatial resoltuion to map nuclear wide chromatin compaction at the level of nucleosome proximity with respect to multiple site specific DSBs. We also demonstrate that when phasor histone FLIM-FRET is coupled with immunofluorescence (IF), this technology has the unique advantage of enabling exploration of any heterogeneity that exists in chromatin structure at the spatially distinct and genetically induced DSBs.